2021
DOI: 10.1021/acsmaterialslett.1c00073
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized MoS2-Based Nanomaterials for Cancer Phototherapy and Other Biomedical Applications

Abstract: Transition-metal dichalcogenides (TMDs), as a novel category of nanomaterials and a potential alternate to graphene, are attracting great interest of researchers, because of their strong conductivity, superior catalytic performance, and good optical properties. As the most representative type of all TMDs, molybdenum disulfide (MoS 2 )-based nanomaterials are expanded into two-dimensional (2D) nanosheets, quantum dots (QDs), flower-like nanoparticles, nanospheres and nanotubes. These types are regarded as promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 282 publications
1
59
0
Order By: Relevance
“…where α is the medium thermal diffusivity. Considering, for instance, the case of a cell with a 10 ÎŒm diameter and using the thermal diffusivity of water (0.143 mm 2 /s at room temperature), the characteristic time is τ T ~0.7 ms. On the other hand, τ T is in an order of a few minutes for R = 10 mm, which is consistent with the typical duration of a PTT on tissues (Chou et al (2013); Carrow et al (2020); Liu et al (2021); Song et al (2017)).…”
Section: Heating At Microscale: Preliminary Considerations and Experi...supporting
confidence: 83%
See 1 more Smart Citation
“…where α is the medium thermal diffusivity. Considering, for instance, the case of a cell with a 10 ÎŒm diameter and using the thermal diffusivity of water (0.143 mm 2 /s at room temperature), the characteristic time is τ T ~0.7 ms. On the other hand, τ T is in an order of a few minutes for R = 10 mm, which is consistent with the typical duration of a PTT on tissues (Chou et al (2013); Carrow et al (2020); Liu et al (2021); Song et al (2017)).…”
Section: Heating At Microscale: Preliminary Considerations and Experi...supporting
confidence: 83%
“…Nowadays, the use of 2D-MoS 2 for photothermal therapy (PTT) has been well assessed ( Wang et al (2021) ). Numerous groups have reported on the effectiveness of properly functionalized 2D-MoS 2 for killing targeted tissues upon irradiation with NIR radiation, in both in vitro and in vivo experiments ( Liu et al (2021) ; Song et al (2017) ). The typical outcome of most of these studies relies on the cell viability following PTT, tumor growth suppression, and/or MoS 2 clearance after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…When added to polymers, it forms composites with improved strength and reduced friction. Previous studies have demonstrated the use of MoS 2 additives in applications, such as lubrication, anti-wear, anticorrosion [ 15 ], and biocompatibility [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a plethora of systematic researches and studies regarding the development of tumor theranostics are gradually increasing in number, and design of polymeric materials as delivery devices in biomedicine has also been systematically summarized in a gradually rising number of reviews [ 6 , [49] , [50] , [51] ]. A detailed and comprehensive overview that introduces nanomaterial integrated polymeric flexible patches in non-cancerous therapy still does not currently exist.…”
Section: Introductionmentioning
confidence: 99%